Simultaneous acquiring and synthesizing images through an optical fiber on a moving mechanism. (10th September 2021) - Lee, Fu-Shin; Lin, Chen-I; Guo, Bo; Chiang, Antony; Ho, Pin-Hsien
Abstract: The research prototypes an optical fiber-scanning mechanism for capturing fiber-acquired multiple images. First, the study develops an image processing firmware embedded in high-speed hardware for image cropping, rotation, sharpening, and stitching, especially synchronizing with the moving mechanism. Then, the embedded firmware successively builds panoramic images while iteratively acquiring images as the mechanism in motion. This research applies a 3D printing technology to prototype the mechanism components and employs servomotors for mechanism motions during the prototyping stage. Next, the mechanism guides the scanning motions to follow prescribed trajectories while capturing images of specified regions. Finally, the research embeds the firmware developed on a Linux OS platform into a high-speed controller board. The resolution tests verify that the best image resolution for the prototyped optical mechanism reaches 14.30 line pairs per millimeter, and the achievable image resolution for an inspected object is 35 μm. Through acquiring and synthesizing images simultaneously by the embedded firmware while the optical fiber-scanning mechanism is in motion, this research demonstrates that the developed system effectively constructs panoramic images for an endoscope device at a lower cost.